The Influence of Baseball Game, Strengthening and Training Motivation on the Motoric Ability of Class V Elementary School 112 Rejang Lebong - Fadhlil Hadi; Asep Sujana Wahyuri; Gusril; Umar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research is a quantitative research with an experimental method using a 2x2 factorial design. The aim of this study was to reveal the effect of playing baseball and bashing accompanied by motivation to practice on improving motor skills. The population in this study were all students of Rejang Lebong 112 Public Elementary School, totaling 290 students. The sample in this study were 32 male students in class V. The statistical analysis used in this study was the two-way ANOVA test to test the hypothesis that baseball games and strength accompanied by motivation to practice have an influence on motor skills. The results showed that 1) There were differences in the motor skills of Rejang Lebong 112 Elementary School students who used the baseball training method and the fortification training method. 2) There is an interaction between training methods and training motivation on motor skills. 3) In the group with high training motivation, the baseball training method was more effective than the strength training method on motor skills. 4) In the low training motivation group, the baseball training method was also more effective than the strength training method on motor skills. The baseball training method is more effective than the fortification training method for motor skills.